Nonsteroidal anti-inflammatory drug-sparing effect of secukinumab in patients with radiographic axial spondyloarthritis: 4-year results from the MEASURE 2, 3 and 4 phase III trials - Dougados, Maxime; Kiltz, Uta; Kivitz, Alan; Pavelka, Karel; Rohrer, Susanne; McCreddin, Suzanne; Quebe-Fehling, Erhard; Porter, Brian; Talloczy, Zsolt (Rheumatology international, 2022)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used to reduce pain and inflammation, and are considered the cornerstone of pharmacological intervention in patients with radiographic axial spondyloarthritis (r-axSpA); however, the long-term use of NSAIDs is debatable due to their restricted therapeutic potential and the risk of side effects and complications. Therefore, reduction in NSAID intake is desirable in r-axSpA patients. Here, we report the long-term NSAID-sparing effect of secukinumab over 4 years in patients with r-axSpA. This post hoc analysis pooled data from 3 secukinumab trials (MEASURE 2-4) for each secukinumab maintenance dose of 150 and 300 mg, regardless of the loading dose regimen being i.v. or s.c. NSAID intake was evaluated prospectively using the Assessment of SpondyloArthritis International Society (ASAS)-NSAID score. Patients with an ASAS-NSAID score > 0 at baseline were analysed. NSAID-sparing endpoints included the mean change in the ASAS-NSAID score, the proportion of patients achieving 50% reduction, and the proportion of patients with an ASAS-NSAID score < 10. Percentages of patients who achieved BASDAI ≤ 2 were also assessed. Overall, 562 patients were included in this pooled analysis (secukinumab: 150 mg, N = 467; 300 mg, N = 95). The mean ASAS-NSAID score decreased with time in both the secukinumab 150 mg and 300 mg dose groups. The proportion of patients who achieved 50% reduction in the ASAS-NSAID score and clinically meaningful reduction of ASAS-NSAID score < 10 increased with time in both dose groups and in both low and high NSAID intake patients. The percentage of patients with a clinically relevant improvement (BASDAI ≤ 2) was consistently higher in patients with an ASAS-NSAID score < 10 than in patients with an ASAS-NSAID score ≥ 10. Secukinumab provided sustained, long-term NSAID-sparing effects in patients with r-axSpA for up to 4 years of treatment, as measured using the ASAS-NSAID score. Trial registered at clinicaltrials.gov: NCT01649375 ( https://clinicaltrials.gov/ct2/show/NCT01649375 ); NCT02008916 ( https://clinicaltrials.gov/ct2/show/NCT02008916 ); NCT02159053 ( https://clinicaltrials.gov/ct2/show/NCT02159053 ).
Keywords: Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Inflammation; NSAID; axiální spondyloartritida; Middle Aged; mužské pohlaví; Biologic disease-modifying antirheumatic drugs; Adult; antiflogistika nesteroidní; Interleukin; ženské pohlaví; Humans; Anti-Inflammatory Agents, Non-Steroidal; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; lidé středního věku; dospělí; nežádoucí účinky léčiv; Axial Spondyloarthritis; Drug-Related Side Effects and Adverse Reactions; Female; Radiographic axial spondyloarthritis; lidé; Male